Applying Implicit Association Test Techniques and Facial Expression Analyses in the Comparative Evaluation of Website User Experience - Mauri, Maurizio; Rancati, Gaia; Gaggioli, Andrea; Riva, Giuseppe (Frontiers in Psychology, 2021)
This research project has the goal to verify whether the application of Neuromarketing techniques such as Implicit Association Test techniques and emotional facial expressions analyses may contribute to the assessment of user experience during and after website navigation. These techniques have been widely and positively applied in assessing customer experience, however little is known about their simultaneous application in the field of user experience. As a specific context, the experience raised by different websites from two well-known automotive brands are compared. 160 Italian university students are enrolled in an online experimental study. Participants perform a BARTT version of Implicit Association Test where the two brands are compared according to different semantic dimensions already used in the automotive field. After completing the BARTT test, participants navigate the target website: 80 participants navigate the first brand website, while the other half navigate the second brand website (between-subject design). During the first 3 minutes of website navigation, emotional facial expressions are recorded. Participants are asked to freely navigate the website home page, look for a car model and its characteristics and price, use the customizing tool and in the end look for assistance. After the website navigation, all participants perform a second time the BARTT version of Implicit Association Test, where the 2 brands are compared again, this time to assess whether the website navigation may impact the Implicit Associations previously detected. A traditional evaluation of the two websites is carried on by means of the classic heuristic evaluation. Findings from this study show, first of all, the significant results provided by Neuromarketing techniques in the field of UX, as Implicit Association Test can provide a positive application for assessing user experience played by brand websites, thanks to the comparison of eventual changes in time reaction between the test performed before and after website navigation exposure. Secondly, results from emotional facial expression analyses during the navigation of both brand websites showed significant differences between the two brands, allowing to predict the emotional impact raised by each website. Finally, the positive correlation with heuristic evaluation shows that Neuromarketing can be successfully applied in UX.